Targeted endometrial cancer therapy as a future prospect - Duangmani Thanapprapasr (2018)
Among female-specific cancers worldwide, endometrial cancer is the third most common after breast cancer and cervical cancer. In addition, it is the most common gynecological cancer in the USA and Europe. The incidence of this disease appears to be increasing. The cause of this increase is multifactorial, but a few possible factors involved are increasing obesity, an aging population leading to more postmenopausal women and greater tamoxifen use. Surgery is generally the primary treatment of this disease and postoperative radiation therapy in some patients with high or intermediate risk may prevent locoregional recurrences. Adjuvant chemotherapy improves progression-free survival in advanced or recurrent cancer. However, overall survival in patients with advanced disease is poor. Hence, better therapy is needed and targeted molecular therapies are emerging as possible treatment candidates. These include molecules that target VEGF, mTOR, tyrosine kinases, human EGF receptors and FGF receptors. Therapies targeting specific molecular features should be evaluated in future strategies in the treatment of endometrial cancer. © 2013 Future Medicine Ltd.